2020
DOI: 10.7717/peerj.8859
|View full text |Cite
|
Sign up to set email alerts
|

The severity of mobile phone addiction and its relationship with quality of life in Chinese university students

Abstract: Objective This study examined the severity of mobile phone addiction and its relationship with quality of life (QOL) in Chinese university students. Methods A total of 2,312 university students from Macao, Hong Kong and mainland China participated in this cross-sectional study. The Mobile Phone Addiction Scale (MPAS), and the World Health Organization Quality of Life-Brief version (WHOQOL-BREF) rating instruments were used to assess the severity of mobile phone addiction and QOL, respectively. Results Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 35 publications
3
41
1
Order By: Relevance
“…For example, high school students with neurotic personality may have obstacles to interpersonal communication due to emotional instability. Mobile phones can make them avoid contact with others to the greatest extent, and in this way can compensate for the lack of information obtained due to the narrow social network [ 36 , 37 ]. The anonymity of using social software on mobile phones can enable them to escape the negative emotions in real life, and moderate use of mobile phones can regulate negative emotions and obtain a sense of happiness [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, high school students with neurotic personality may have obstacles to interpersonal communication due to emotional instability. Mobile phones can make them avoid contact with others to the greatest extent, and in this way can compensate for the lack of information obtained due to the narrow social network [ 36 , 37 ]. The anonymity of using social software on mobile phones can enable them to escape the negative emotions in real life, and moderate use of mobile phones can regulate negative emotions and obtain a sense of happiness [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatehi et al [ 36 ] in Iran showed that IA decreased the QOL in physical, psychological, and social dimensions [ 36 ]. The results of three studies in Taiwan [ 37 ], China [ 49 ], and the USA [ 38 ] indicated that IA decreased the QOL in physical, social, psychological, and environmental aspects. In addition to a small number of cross-sectional studies, which make the comparison and deduction of causal relationships difficult, differences in contexts and ignorance of the underlying factors affecting the QOL dimensions (such as unemployment, chronic diseases, mental/psychological disorders (depression, negative feelings, and stress)) can be considered as reasons for the contradiction between results on the Internet impact on QOL dimensions [ 45 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For excessive smartphone use, i.e., long usage times without considering symptoms of behavioural addiction, associations with poorer sleep quality [ 32 ], bad mood [ 33 ], low psychological well-being [ 34 ] and behavioural and emotional problems [ 35 ] were observed. It is important to mention that most previous studies on PSU were performed in Asian countries (especially South Korea [ 36 ]) and in older adolescents or young adults [ 15 , 17 , 28 ]. They reported that a high number of adolescents (mean age 15.6 years) in South Korea showed PSU (30.9%) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%